2020
DOI: 10.1074/jbc.ra120.014851
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial oxidative metabolism attenuates EMCV replication and protects β-cells from virally mediated lysis

Abstract: Viral infection is one environmental factor that may contribute to the initiation of pancreatic β-cell destruction during the development of autoimmune diabetes. Picornaviruses, such as encephalomyocarditis virus (EMCV), induce a pro-inflammatory response in islets leading to local production of cytokines, such as IL-1, by resident islet leukocytes. Furthermore, IL-1 is known to stimulate β-cell expression of iNOS and production of the free radical nitric oxide. The purpose of this study was to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 78 publications
3
13
0
Order By: Relevance
“…Generally, cytokines and nitric oxide are viewed as damaging to β-cells based on observations that exogenous IL-1β treatment impairs oxidative phosphorylation and insulin secretion and eventually causes β-cell death with prolonged exposure in a nitric oxide–dependent manner ( Mandrup-Poulsen et al, 1985 ; Bendtzen et al, 1986 ; Southern et al, 1990 ; Welsh et al, 1991 ; Corbett & McDaniel, 1992 , 1995 ; Corbett et al, 1992a, 1993 ; Cunningham & Green, 1994 ; Mandrup-Poulsen, 1996 ). However, our recent studies suggest that the ability of nitric oxide to inhibit mitochondrial oxidation and ATP generation protects β-cells from apoptosis ( Oleson et al, 2016 ) and viral infection ( Stafford et al, 2020 ). Our observations here that IL-1β induces antiviral genes ( Fig 3 ) and fails to induce apoptotic mediators ( Fig S4 ) dovetail with these recent findings and further support the idea that the primary functions of IL-1β and nitric oxide are to protect β-cells from damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, cytokines and nitric oxide are viewed as damaging to β-cells based on observations that exogenous IL-1β treatment impairs oxidative phosphorylation and insulin secretion and eventually causes β-cell death with prolonged exposure in a nitric oxide–dependent manner ( Mandrup-Poulsen et al, 1985 ; Bendtzen et al, 1986 ; Southern et al, 1990 ; Welsh et al, 1991 ; Corbett & McDaniel, 1992 , 1995 ; Corbett et al, 1992a, 1993 ; Cunningham & Green, 1994 ; Mandrup-Poulsen, 1996 ). However, our recent studies suggest that the ability of nitric oxide to inhibit mitochondrial oxidation and ATP generation protects β-cells from apoptosis ( Oleson et al, 2016 ) and viral infection ( Stafford et al, 2020 ). Our observations here that IL-1β induces antiviral genes ( Fig 3 ) and fails to induce apoptotic mediators ( Fig S4 ) dovetail with these recent findings and further support the idea that the primary functions of IL-1β and nitric oxide are to protect β-cells from damage.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the observation that cytokine-induced nitric oxide promotes heat shock protein expression in rat islets ( Helqvist et al, 1991 ), our results suggest that the heat shock response may provide an internal “off switch” to prevent cytokine-mediated islet damage after protective signaling has been initiated. In other words, nitric oxide may not only protect β-cells through inhibition of mitochondrial oxidation ( Oleson et al, 2016 ; Stafford et al, 2020 ), but may also provide a means to shut down prolonged cytokine signaling, which is known to be damaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While additional studies are required to more fully appreciate the roles of nitric oxide production in regulating DDR signaling in β-cells, our studies are beginning to shed light on the physiological roles for cytokine signaling, iNOS expression and the production of nitric oxide by β-cells. On such role being the inhibition of picornavirus replication in a pancreatic β-cell selective manner (67,68). Cell culture and islet isolation.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In reevaluating these contrasting responses, we reasoned that cytokine signaling in β-cells could play a physiologically protective role in promoting β-cell survival, and in support of this hypothesis, we have recently shown that nitric oxide attenuates EMCV replication in insulinoma MIN6 cells and mouse islets by inhibiting mitochondrial oxidative metabolism ( 25 ). Inhibitors of the electron transport chain and mitochondrial uncouplers attenuate EMCV replication and EMCV-mediated MIN6 cell lysis in a manner like nitric oxide.…”
mentioning
confidence: 99%